(untitled) (Research, Society and Development, 2022)
The present article aims at understanding the woman, as a social and historical subject, which is formed from the ideology and culture imposed by a class-based society. The main purpose is to analyze the ideology disseminated in the magazine Illustração Pelotense, in the beginning of the 20th century, under the perspective of information targeted at the female public, through the press. The emerging theme was the domestic work, which we discussed in three topics. First, we approached the naturalization of housework for women in the capitalist society, through the press. Therefore, we see the woman as being brought up, since childhood, to strictly play her role as wife, mother and maid. Also, we noticed class discrimination, as the wordings pointed out to a subjugation of the housework done by women from the rich women to the subordinate classes, as well as the depreciation of these bodies. After that, we discussed about the female education directed at submission and subservience as a love act. In the last topic we focused on the racial discrimination, through the perception of the deletion of the black woman in the magazine. Thus, we understand that, even after being freed, she was kept excluded, taking the less prestigious social and professional places. At the end of the analysis, we observed the press from Pelotas, at the time, acting through the labels of sex, race and class discrimination in the capitalist society.